Analisis Kelayakan Finansial Usahatani Kopi Arabika - Rachman, Syifa Maghfirah; Abubakar, Abubakar; Nur’azkiya, Luthfi (Peneliti.net, 2025)
Giri Mekar Giri Mekar Village, as one of the coffee producers managed by the Giri Senang Forest Farmers Group. There are several obstacles to the development of coffee plants, namely climate change which can cause production to decline and a lack of business capital. The aim of this research is to determine revenue costs and income, determine the feasibility of farming and analyze the level of sensitivity to Arabica coffe farming. The analysis method used is through the NPV, IRR, NET B/C, and Payback Period values as well as sensitivity to production quantities, selling prices. The research carried out resulted in income of IDR 16,004,000 one year and income during the research of IDR 14,915,200 in one year. The NPV value obtained wa IDR 50,694,437, the IRR was 73%, the NET B/C was 10,65 and the Payback Period was 3,58 years. The level of sensitivity value to revenue has a maximum limit of 12% for price reductions, 11% reduction in production quantities and 9% increases in production costs. Arabica coffee plantations show that farming is still worth pursuing.